2010
DOI: 10.1021/jp102353q
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Electronic Spaces for Modeling Donor/Acceptor Interactions

Abstract: Diabatic states for donor (D) and acceptor (A) interactions in electron transfer (ET) processes are formulated and evaluated, along with coupling elements (H DA ) and effective D/A separation distances (r DA ), for reduced electronic spaces of variable size, using the generalized Mulliken Hush model (GMH), applicable to an arbitrary state space and nuclear configuration, and encompassing Robin-Day class III and as well as class II situations. Once the electronic state space is selected (a set of n g 2 adiabati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…Following the treatments presented previously, 39 we determined the width of the polarons based on the differences of ESP charge distributions between anions and neutrals as well as on the electron density in the SOMO of the anions (Table 2 and Supporting Information Table S1). A full density of the anion SOMO serves as a plausible zeroth-order estimate of the different densities of electrons to the extent that addition of an electron to the neutral does not 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 appreciably polarize the 'core' defined by the occupied neutral orbitals.…”
Section: Widths Of Polaronsmentioning
confidence: 99%
“…Following the treatments presented previously, 39 we determined the width of the polarons based on the differences of ESP charge distributions between anions and neutrals as well as on the electron density in the SOMO of the anions (Table 2 and Supporting Information Table S1). A full density of the anion SOMO serves as a plausible zeroth-order estimate of the different densities of electrons to the extent that addition of an electron to the neutral does not 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 appreciably polarize the 'core' defined by the occupied neutral orbitals.…”
Section: Widths Of Polaronsmentioning
confidence: 99%
“…Scheme 1) and higherenergy "intermediate" structures with different configurations of the charge and pairing degrees of freedom. 55,56 The essential physics was described by Moffitt, who invoked the formamidinum cation as an explicit example. 57 The π orbital system of the formamidinum cation has four π electrons distributed amongst three p orbitals.…”
Section: A Charge/bond-resonance In Michler's Hydrol Blue (Hb)mentioning
confidence: 99%
“…31 They found that V DA computed with the twostate model ''involves crucial mixing with intervening bridge states'' and an increasingly larger number of adiabatic states included in the GMH scheme lead to V DA approaching the through-space coupling values. 31 In the paper we consider model D-B-A systems to explore the performance of a two-state FCD scheme. We show that derived V DA values account properly for both the direct and superexchange interactions even when the tunneling gap is small.…”
Section: Introductionmentioning
confidence: 99%